2012
DOI: 10.1111/j.1466-7657.2012.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction of nurses in a Saudi Arabian university teaching hospital: a cross‐sectional study

Abstract: These findings indicate that there is a need to increase nurses' salaries and bonuses for extra duties. More training programmes and further education also should be encouraged for all nurses. Therefore, it is imperative that nursing managers and policy makers in Saudi Arabia consider these findings to improve nurses' job satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 25 publications
9
54
1
6
Order By: Relevance
“…The satisfaction with other subscales was the same for both males and females. Similarly, AlDossary et al [21] found no significant relationship between gender and job satisfaction. This is perhaps because the males were only 11.3% of the population, there may not have been sufficient gender diversity to detect the differences.…”
Section: Comparison Between Gender and Job Satisfactionmentioning
confidence: 93%
See 1 more Smart Citation
“…The satisfaction with other subscales was the same for both males and females. Similarly, AlDossary et al [21] found no significant relationship between gender and job satisfaction. This is perhaps because the males were only 11.3% of the population, there may not have been sufficient gender diversity to detect the differences.…”
Section: Comparison Between Gender and Job Satisfactionmentioning
confidence: 93%
“…Flexibility with scheduling gives them time to attend to other personal matters and nurses are satisfied by convenient job schedules that allow them to meet their personal and family needs. [21] 4.4 Satisfaction with main subscales From the six subscales, three were hygiene factors. These were: professional work environment, professional relationships and benefits.…”
Section: Subscales Correlationsmentioning
confidence: 99%
“…3 Job satisfaction is important in healthcare organisations because it is an indicator of the physical and psychological states of employees. 4 The attitude that a nurse holds towards patients and their state of ill health strongly determines the quality and extent of the emotional, physical, and psychological help that patients receive from that nurse. 5 Attitude is an evaluative disposition; a tendency to like or dislike, or to act favourably or unfavourably towards someone or something, which might have an impact on the way someone behaves towards that person or object.…”
Section: Introductionmentioning
confidence: 99%
“…Several research studies have been conducted in the KSA investigating job stress, working conditions, and job satisfaction among Saudi and IENs working in both privately and publicly funded hospitals. These studies focused on individual nurse-variables such as burnout and intention to stay [38,56] and organizational variables, such as leadership style, organizational commitment, recognition, and hospital performance [44,61,62,63]. According to these studies, the difficult working conditions experienced by nurses practicing in the KSA reported on work overloads, lack of recognition, organizational support, and poor salaries that commonly lead to burnout, job stress, and job dissatisfaction.…”
Section: Oncology Nursing Care In Saudi Arabia Contextmentioning
confidence: 99%